Participatory workshops : - Chambers, Robert (Earthscan Publications, 2002)
Making participation real requires workshops, training and learning that are themselves participatory. This sourcebook presents the results of the author's vast experience in the form of twenty-one sets of ideas, activities and tips, both serious and fun, for topics such as getting started, seating, forming groups, managing large numbers, analysis, feedback, evaluation and ending.